2003
DOI: 10.1291/hypres.26.923
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Membrane-Bound Catechol-O-Methyltransferase in the Liver of Spontaneously Hypertensive Rats

Abstract: We have previously reported that methylation of catecholamines by catechol-O-methyltransferase (COMT)washighly sensitive method to measure NE and NMN (7-9). Using this method, we demonstrated that methylation of catecholamines by COMT in SHR was attenuated during acute hypotension, when compared to that in WKY rats. Furthermore, intravenous administration of S-adenosyl-L-methionine (SAMe), a coenzyme for COMT, lowered blood pressure in SHR with a concomitant increase of NMN (10).Since COMTs exist in most tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…study confirmed those previous results. It was reported that COMT expression in the kidney in 23-week-old SHR rats was greater than that in control WKY rats (Tsunoda et al 2003). In our experiments, we found that early onset of brain stroke (around 11 weeks) was characteristic in M-SHRSP rats and the rats died of brain stroke at around 15 weeks.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…study confirmed those previous results. It was reported that COMT expression in the kidney in 23-week-old SHR rats was greater than that in control WKY rats (Tsunoda et al 2003). In our experiments, we found that early onset of brain stroke (around 11 weeks) was characteristic in M-SHRSP rats and the rats died of brain stroke at around 15 weeks.…”
Section: Discussionsupporting
confidence: 55%
“…Transcription of the COMT gene is controlled by two distinct promoters (Männistö and Kaakkola 1999). Polypeptide is translated from the shorter transcript, soluble COMT, whereas a longer mRNA from the P2 promoter encodes mainly membrane-bound COMT (MB-COMT) (Tsunoda et al 2003). The molecular mass of COMT detected by western blot analysis was 24 kDa, and this COMT was considered to be the soluble form of rat COMT.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] However, there is a difference in their magnitudes: MB-COMT activities were only 2-5 times lower than S-COMT activities in the brain but were 15-25 times lower in the liver and the kidney. Considering the results obtained in the difference of affinities for COMT described below, MB-COMT in the brain may play a more important role than other peripheral tissues.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous studies we found that both the activity and protein expression of MB-COMT were lower in the liver of spontaneously hypertensive rats (SHR) than in the liver of Wistar-Kyoto (WKY) rats ( 11 ). We hypothesized that this reduced activity of MB-COMT is involved in the development of hypertension by increasing the local NE content.…”
Section: Introductionmentioning
confidence: 95%